Acute intranasal osteopontin treatment in male rats following TBI increases the number of activated microglia but does not alter lesion characteristics. Issue 1 (20th March 2019) - Jullienne, Amandine; Hamer, Mary; Haddad, Elizabeth; Morita, Alexander; Gifford, Peter; Hartman, Richard; Pearce, William J.; Tang, Jiping; Zhang, John H.; Obenaus, Andre
Abstract: Intranasal recombinant osteopontin (OPN) has been shown to be neuroprotective in different models of acquired brain injury but has never been tested after traumatic brain injury (TBI). We used a model of moderate‐to‐severe controlled cortical impact in male adult Sprague Dawley rats and tested our hypothesis that OPN treatment would improve neurological outcomes, lesion and brain tissue characteristics, neuroinflammation, and vascular characteristics at 1 day post‐injury. Intranasal OPN administered 1 hr after the TBI did not improve neurological score, lesion volumes, blood–brain barrier, or vascular characteristics. When assessing neuroinflammation, we did not observe any effect of OPN on the astrocyte reactivity but discovered an increased number of activated microglia within the ipsilateral hemisphere. Moreover, we found a correlation between edema and heme oxygenase‐1 (HO‐1) expression which was decreased in OPN‐treated animals, suggesting an effect of OPN on the HO‐1 response to injury. Thus, OPN may increase or accelerate the microglial response after TBI, and early response of HO‐1 in modulating edema formation may limit the secondary consequences of TBI at later time points. Additional experiments and at longer time points are needed to determine if intranasal OPN could potentially be used as a treatment after TBI where it might be beneficial by activating protective signaling pathways. Abstract : This study showed that following traumatic brain injury (TBI) in male rats, intranasal osteopontin (OPN) treatment induced no change in lesion size and blood–brain barrier (BBB) disruption 1 day post‐injury. However, we described an increased number of activated microglia and increased variability in the heme oxygenase‐1 response to the injury.